Effect of Noug Seed Cake (Guizotia Abssinica) With Local Brewery (Areke Atella) on Reproductive Performance and Body Weight Gain of Bonga Breed Ram in Kaffa Zone, Southwest Ethiopia - Gebre, Agegnehu (Bonga University, 2024)
The study was conducted to assess the impact of replacing noug seed cake with areke atella, on testicular parameters, semen characteristics, and body weight gain in Bonga breed rams. A total of 48 rams were selected purposively from individual members of Boka community based breeding program (CBBP. Data were analyzed by using SAS Software version 9.3 and least significance difference (LSD) was used for statistically significant level among categorical variables and performance data were subjected to analysis of variance (ANOVA) GLM procedure of SAS 9.3 software. The experimental design involved eight black and six groups (T1, T2, T3, T4, T5, and T6) of 8 -12 month old rams based on body condition and age, employing a randomized complete block (RCBD) design. The control group (T6) remained unaltered; while T1 received 100% noug seed cake, T2 had 25% areke atella and 75 % noug seed cake. T3, 50% areke atella and 50% noug seed cake, T4 had 75% areke atella, 25% noug seed cake and T5 received 100% substitution of areke atella, respectively. Desho grass also served as roughage, and provided ad-libitum to all rams. The study spanned for 28 days with an additional 14-day adaptation phase, from August 26th, 2023 to September 22rd, 2023. After adaptation period for the feed. Semen samples were collected from each experimental ram (initial and final) using an artificial vagina. Fresh semen analysis revealed significant improvements in semen volume, sperm concentration, sperm motility, and colour in replacement groups (T1, T2, T3, T4 and T5) compared to the group (T6). Similarly, the replacement groups observed increased body weight and scrotal circumference (p<0.05). Moreover, all examined variables within the replacement groups found no significant differences (P>0.05). Notably, the body weight of rams positively correlated with scrotal circumference (r=0.54) and semen volume (r=0.58). Replacing areke atella with noug seed cake in the diet of Bonga breed rams has been found to enhance both their scrotal circumference and body weight gain. The replacement groups (T1, T2, T3, T4 and T5) demonstrated superior semen quality, increased body weight and larger scrotal circumference than the control group (T6). Additionally, T2 emerged as the most effective for improving weight gain, semen quality, and scrotal circumference in Bonga breed rams.